The effect of neuropathy exercises on decreasing the value of 10-gr monofilament in patients with Type 2 Diabetes Mellitus - Bakara, Derison Marsinova Bakara; Fatimah Khoirini; Kurniyati (Nursing and Health Sciences Journal (NHSJ), 2025)
The most common chronic complication in people with type 2 diabetes mellitus is diabetic peripheral neuropathy (DPN). DPN can occur in one in five people with type 2 diabetes mellitus. This study aims to see the effect of neuropathy exercises on assessing symptoms of DPN using 10-gr monofilament. Methods: This research was quantitative research with a Pretest-Posttest one-group design approach, which aimed to see the effect of neuropathy exercises on reducing the assessment of symptoms of DPN using 10-gr monofilament. The intervention carried out for people with type 2 diabetes mellitus was neuropathy exercises. In the pretest, Type 2 diabetes mellitus patients were assessed for symptoms of DPN using 10-gr monofilament. Then, neuropathy exercise intervention was given to the left and right legs, carried out daily for 15 minutes for 6 weeks. In the posttest, symptoms of DPN were assessed on the left and right foot using 10-gr monofilament. Results: The study showed that neuropathy exercises reduced the value of DPN symptoms in the left and right legs using 10-gr monofilament. Before the neuropathy exercise intervention, the value of neuropathy symptoms using 10-gr monofilament was Mean ± SD 10.42 ± 12.877; after the neuropathy exercise intervention, the value of neuropathy symptoms using 10 gr monofilament was 9.88 ± 2.904 with a value of p=0.01. Neuropathy exercises can be done as an alternative measure for the treatment of symptoms of DPN using 10-gr monofilament in patients with type 2 diabetes mellitus. It is recommended that neuropathy exercises be one of the protocols for reducing hyperglycemia and reducing complications of type 2 diabetes mellitus, such as symptoms of DPN.